Effective cataract surgical coverage in adults aged 50 years and older: estimates from population-based surveys in 55 countries. Issue 12 (December 2022) - McCormick, Ian; Butcher, Robert; Evans, Jennifer R; Mactaggart, Islay Z; Limburg, Hans; Jolley, Emma; Sapkota, Yuddha D; Oye, Joseph Enyegue; Mishra, Sailesh Kumar; Bastawrous, Andrew; Furtado, João M; Joshi, Anagha; et al.
Summary: Background: Cataract is the leading cause of blindness globally. Effective cataract surgical coverage (eCSC) measures the number of people in a population who have been operated on for cataract, and had a good outcome, as a proportion of all people operated on or requiring surgery. Therefore, eCSC describes service access (ie, cataract surgical coverage, [CSC]) adjusted for quality. The 74th World Health Assembly endorsed a global target for eCSC of a 30-percentage point increase by 2030. To enable monitoring of progress towards this target, we analysed Rapid Assessment of Avoidable Blindness (RAAB) survey data to establish baseline estimates of eCSC and CSC. Methods: In this secondary analysis, we used data from 148 RAAB surveys undertaken in 55 countries (2003–21) to calculate eCSC, CSC, and the relative quality gap (% difference between eCSC and CSC). Eligible studies were any version of the RAAB survey conducted since 2000 with individual participant survey data and census population data for people aged 50 years or older in the sampling area and permission from the study's principal investigator for use of data. We compared median eCSC between WHO regions and World Bank income strata and calculated the pooled risk difference and risk ratio comparing eCSC in men and women. Findings: Country eCSC estimates ranged from 3·8% (95% CI 2·1–5·5) in Guinea Bissau, 2010, to 70·3% (95% CI 65·8–74·9) in Hungary, 2015, and the relative quality gap from 10·8% (CSC: 65·7%, eCSC: 58·6%) in Argentina, 2013, to 73·4% (CSC: 14·3%, eCSC: 3·8%) in Guinea Bissau, 2010. Median eCSC was highest among high-income countries (60·5% [IQR 55·6–65·4]; n=2 surveys; 2011–15) and lowest among low-income countries (14·8%; [IQR 8·3–20·7]; n=14 surveys; 2005–21). eCSC was higher in men than women (148 studies pooled risk difference 3·2% [95% CI 2·3–4·1] and pooled risk ratio of 1·20 [95% CI 1·15–1·25]). Interpretation: eCSC varies widely between countries, increases with greater income level, and is higher in men. In pursuit of 2030 targets, many countries, particularly in lower-resource settings, should emphasise quality improvement before increasing access to surgery. Equity must be embedded in efforts to improve access to surgery, with a focus on underserved groups. Funding: Indigo Trust, Peek Vision, and Wellcome Trust.